1993
DOI: 10.1159/000282483
|View full text |Cite
|
Sign up to set email alerts
|

MR Angiography of Renal Cell Carcinoma

Abstract: Seventeen patients with renal cell carcinoma were studied to evaluate the usefulness of gradient echo (fast low-angle shot), time-of-fiight magnetic resonance (MR) angiography under breath-holding. By reconstruction of the data of consecutive coronal scans of the abdomen, in all 17 patients with renal cell carcinoma, MR angiography can delineate the abdominal aorta, inferior vena cava and renal arteries and veins simultaneously without any contrast materials. Our present study suggested that MR angiography is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additionally, gradient-echo acquisitions have been shown to allow accurate visualization of venous thrombosis. Gradient-echo pulse sequences with fast acquisition times permit examinations within short breath-holding times [2,15,16,17]. Dual-phase MR angiography has recently demonstrated its capabilities to diagnose venous invasion at the same time that it depicts the arterial supply of renal carcinoma [18].…”
mentioning
confidence: 99%
“…Additionally, gradient-echo acquisitions have been shown to allow accurate visualization of venous thrombosis. Gradient-echo pulse sequences with fast acquisition times permit examinations within short breath-holding times [2,15,16,17]. Dual-phase MR angiography has recently demonstrated its capabilities to diagnose venous invasion at the same time that it depicts the arterial supply of renal carcinoma [18].…”
mentioning
confidence: 99%
“…DEBATIN et al have shown that 2-D PC resulted in a 60% error rate when evaluating potential kidney donors (11). In addition to renal artery stenosis, MRA has been used to assess the renal vascular structure in renal cell carcinoma and renal infarction (65,70). Physiological alterations in the renal function can be studied by measuring the renal blood flow by MRA.…”
Section: Clinical Resultsmentioning
confidence: 99%